Photobiomodulation as a strategy for the treatment of recurrent aphthous stomatitis - Case Report (Research, Society and Development, 2026)
Recurrent Aphthous Stomatitis (RAS) is characterized as a common pathology in the oral cavity that causes discomfort on patients and that impairs several daily functions. Therefore, this study aimed to analyze 2 clinical cases of RAS submitted to photobiomodulation therapy (PBM) and discuss the benefits that it provides over ulcerations and reactions caused in the tissue. The patients sought the extension project “Laserterapia na Odontologia” in a dental service, in which it was performed the anamnesis and detailed clinical examination, providing attention to their main complaint, at the end it was possible to observe the presence of whitish ulcerative lesions surrounded by a red area and with painful symptoms, which confirms the diagnosis of RAS, then it was decided to use the PBM for a treatment for these lesions,  with a protocol for pain and another for acceleration of the wound healing period. It was observed that the immediate reduction of the painful symptomatology in both cases, just as the disappearance of the lesion approximately 3 days after the first irradiation. The PBM was effective in the treatment for RAS in both reported cases and its modulating action of inflammation, analgesic and tissue repair are established, favoring a non-invasive treatment, since it dispensed the use of systemic medications.